2014
DOI: 10.1371/journal.pone.0095865
|View full text |Cite
|
Sign up to set email alerts
|

Viral Infection Is Not Uncommon in Adult Patients with Severe Hospital-Acquired Pneumonia

Abstract: BackgroundViral pathogens have not generally been regarded as important causes of severe hospital-acquired pneumonia (HAP), except in patients with hematologic malignancy or transplant recipients. We investigated the role and distribution of viruses in adult with severe HAP who required intensive care.MethodsFrom March 2010 to February 2012, adult patients with severe HAP required admission to the intensive care unit (ICU), 28-bed medical ICU in a tertiary care hospital, were prospectively enrolled. Respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 37 publications
3
69
1
7
Order By: Relevance
“…10 It has also been reported that respiratory viruses were responsible for 22.5% of cases of severe hospital-acquired pneumonia requiring ICU admission in adults. 11 These results strongly suggest that hospital-acquired infections caused by respiratory viruses could lead to serious consequences.…”
Section: Discussionmentioning
confidence: 96%
“…10 It has also been reported that respiratory viruses were responsible for 22.5% of cases of severe hospital-acquired pneumonia requiring ICU admission in adults. 11 These results strongly suggest that hospital-acquired infections caused by respiratory viruses could lead to serious consequences.…”
Section: Discussionmentioning
confidence: 96%
“…The identified viruses were respiratory syncytial virus (6.1%), parainfluenza virus (6.1%), influenza virus (3.8%), cytomegalovirus (1.9%), human coronavirus (1.5%), bocavirus (0.8%), human metapneumovirus (0.8%), and adenovirus (0.4%). 28 These data underscore the importance of infection control measures in patients with pneumonia.…”
Section: Epidemiology Of Hospital-acquired Viral Respiratory Infectionmentioning
confidence: 94%
“…[7][8][9] Although no studies have reported the incidence of ARDS specifically caused by viral pneumonia, epidemiologic surveys of adults admitted to the intensive care unit (ICU) with pneumonia and respiratory failure suggest that respiratory viruses are a common cause of severe pneumonia. 10,11 In the Etiology of Pneumonia in the Community (EPIC) study, a population-based surveillance for CAP, respiratory viruses were identified in 22% of adults admitted to the ICU with radiographically proven pneumonia. 12 In a prospective, observational study of consecutive patients admitted to an ICU with CAP in 6 hospitals in Kentucky, respiratory viruses were identified in 23% of adults.…”
Section: Epidemiologymentioning
confidence: 99%